Chemical Constituents from Campylotropis hirtella - Xie, Yang-Guo; Li, Tao; Wang, Guo-Wei; Ren, Jie; Wang, Xing; Pan, Ya-Ping; Li, Hui-Liang; Yan, Shi-Kai; Jin, Hui-Zi; Zhang, Wei-Dong (Planta Medica, 2016)
A phytochemical investigation on the roots of Campylotropis hirtella afforded nine new isoflavones (3–9, 12, 15), two new isoflavans (10 and 11), one new coumestan (1), and three new prenylated benzoic acid derivatives (2, 13, 14), together with twenty-four known compounds. Their structures were established by spectroscopic analysis and circular dichroism data. The isolated compounds were also evaluated for their antibacterial activities against Enterococcus faecalis, Salmonella gallinarum, Streptococcus suis, Streptococcus agalactiae, Aeromonas hydrophila, Pseudomonas aeruginosa, Bacillus subtilis, Riemerella anatipestifer, and Vibrio alginolyticus.
Keywords: Campylotropis hirtella; Leguminosae; flavonoids; antibacterial activities